CTIM-15. FIRST-IN-HUMAN PHASE 1 STUDY OF CD200 ACTIVATION RECEPTOR-LIGAND (CD200AR-L) AND ALLOGENEIC TUMOR LYSATE VACCINE IMMUNOTHERAPY FOR RECURRENT GLIOBLASTOMA: INITIAL RESULTS FROM AN ONGOING CLINICAL TRIAL. (12th November 2021) - Neil, Elizabeth; Eaton, Anne; Lunn, Shannon; Nelson, Kristen; Greengard, Emily; Moertel, Christopher; Olin, Michael
Abstract: BACKGROUND: Poor efficacy and adverse events limit the use of immunotherapy in the treatment of glioblastoma. CD200AR-L, a novel immunotherapy targeting multiple checkpoints with a single peptide inhibitory ligand, activates the immune system by downregulating CD200-inhibitory receptor, PD-1/PD-L1, and CTLA-4. METHODS: Single-center, first-in-human, dose-escalation phase 1 clinical trial (NCT04642937) utilizing a 3 + 3 design initiated accrual in 12/2020 at dose level-1; CD200AR-L 3.75micrograms/kg/dose administered on days 1 and 2 by intradermal injection after topical imiquimod. On day 2, a fixed dose of an allogeneic vaccine is also injected intradermally. Induction Phase consists of this injection series weekly for 4 weeks with monitoring for dose-limiting toxicity through day 28. RESULTS: Between 12/2020 to 3/2021, 6 patients were enrolled on dose level-1; aged 37-65 years, 4 men, all with KPS >/= 80, and 3 patients on daily dexamethasone (4mg (n=2), 2mg (n=1)). Five were at first recurrence, 1 at second and 5 had cancers MGMT-promoter unmethylated. All completed the 4 weeks of induction. One dose-limiting toxicity of a grade-III encephalopathy was observed. Non-dose-limiting grade-III toxicities included, lymphopenia (n=1) and immunotherapy-related intracranial edema (IrICE) (n=2). IrICE symptoms were temporarily mitigated with 'bevacizumab rescue protocol.' No patients had local injection site reactions. Three patients are off study for radiographic disease progression confirmed on pathology (n=1) and radiographic disease progression with progressive neurological decline (n=2). Completed investigational hematologic immune monitoring for 4/6 patients revealed, that between weeks 2 and 4 post-vaccination, evidence of immune stimulation with an increase in CD4/8 T-cells, natural killer, and natural killer T-cells. There was also a reduction in immunosuppressants noted by a decrease in PD-1/PD-L1 and CTLA-4 expression on CD4/8 T-cells, CD14, CD11c, and myeloid-derived suppressor cells. CONCLUSION: Initial dosing of CD200AR-L was well tolerated with early positive signal of immunological effect. Enrollment continues, now at dose level-2; CD200AR-L at 5micrograms/kg/dose.